Anterior versus posterior retractor reinsertion with a lateral tarsal strip for involutional entropion repair: A multicentric experience - Mateos-Olivares, Milagros (2023)
Purpose: The aim was the comparison of two different approaches to re-insert the inferior eyelid retractors within addition to lateral tarsal strip at lower eyelid involutional entropion (LEIE) surgical correction. Method: This multicentric retrospective case series involved 233 consecutive patients (195 eyelids) who underwent LEIE repair. All the lids had a lateral tarsal strip (LTS) in addition to the reinsertion of retractors onto the tarsal plate via the anterior approach (group 1) or the posterior approach (group 2). The desired normal position of the eyelids at 6-month follow-up was considered ‘surgical successes, while entropion recurrence and overcorrection (ectropion) were considered ‘surgical failures’. Results: One-hundred ninety-one (82%) surgeries were included in group 1 and 42 (18%) in group 2. The success rate was 92.1% (176 lids) in group 1 and 85.7% (36 lids) in group 2 (p = 0.188). The recurrence rate was statistically higher for group 2 (14.3%) than for group 1 (3.7%) (p = 0.016). Overcorrection only described in group 1 (3.1%). Both groups had a similar complication rate (p = 0.268), with trichiasis being the most frequent (14, 6%). Ten eyelids (47.6%) from the 21 overall failures were satisfactorily reoperated, and the remaining ones were treated conservatively. Conclusion: The anterior or posterior approach to reinsert lower eyelid retractors to tarsal plate in addition to LTS to correct LEIE can provide a similar outcome. However, the anterior approach achieves a slightly higher success rate with fewer recurrences but with a higher overcorrection rate.